1999
DOI: 10.1038/sj.bjc.6690736
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of liver metastases with photodynamic therapy, using the second-generation photosensitizer meta-tetra(hydroxyphenyl)chlorin (mTHPC), in a rat model

Abstract: SummaryThe only curative treatment for patients with liver metastases to date is surgery, but few patients are suitable candidates for hepatic resection. The majority of patients will have to rely on other treatment modalities for palliation. Photodynamic therapy (PDT) could be a selective, minimally invasive treatment for patients with liver metastases. We studied PDT in an implanted colon carcinoma in the liver of Wag/Rij rats, using the photosensitizer meta-tetra(hydroxyphenyl)chlorin (mTHPC). mTHPC tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
2
21
0
1
Order By: Relevance
“…As one of the second-generation photosensitizers, mesotetrakis(4-hydroxyphenyl)porphyrin (THPP, Fig. 1) with high photosensitivity and organic selectivity may be used as a potential drug molecule in PDT for anticancer treatment, and indeed a recent report has shown that THPP can destroy intrahepatic tumors with better efficacies and fewer side effects [12].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the second-generation photosensitizers, mesotetrakis(4-hydroxyphenyl)porphyrin (THPP, Fig. 1) with high photosensitivity and organic selectivity may be used as a potential drug molecule in PDT for anticancer treatment, and indeed a recent report has shown that THPP can destroy intrahepatic tumors with better efficacies and fewer side effects [12].…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of MB to tumor tissue is high and depends on a precise local injection of the dye. This study demonstrates that m-THPC is retained in an intrahepatic CRC cell tumors and that m-THPC-mediated experimental PDT is capable of inducing remission of metastatic colon tumors in the liver [115].…”
Section: Photodynamic Effects Of Different Photosensitizers Toward Crmentioning
confidence: 96%
“…It has been considered as a promising technique for curative or palliative treatment of many different types of cancer [2].…”
Section: Introductionmentioning
confidence: 99%